Editorial (Journal of Forest and Livelihood, 2001)
The Dimensions of forestry and livelihoods are many, and no single perspective, strategy and sets of actions can address it fully. we all still have to learn and act together. we should reflect, review and share what we have learned in different times, context and interventions. we should do this at various levels - from local to global as livelihoods and communities are increasingly affected by a wide array of forces.